Elexacaftor/Tezacaftor/Ivacaftor improves bronchial artery dilatation detected by magnetic resonance imaging in patients with cystic fibrosis - Wucherpfennig, Lena; Triphan, Simon M. F.; Wege, Sabine; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Sommerburg, Olaf; Stahl, Mirjam; Mall, Marcus A.; Eichinger, Monika; Wielpütz, Mark Oliver (Annals of the American Thoracic Society, 2023)
Rationale: Magnetic resonance imaging (MRI) detects improvements in mucus plugging and bronchial wall thickening, but not in lung perfusion in patients with cystic fibrosis (CF) treated with elexacaftor/tezacaftor/ivacaftor (ETI). - - Objectives: To determine whether bronchial artery dilatation (BAD), a key feature of advanced lung disease, indicates irreversibility of perfusion abnormalities and whether BAD could be reversed in CF patients treated with ETI. - - Methods: A total of 59 adults with CF underwent longitudinal chest MRI, including magnetic resonance angiography twice, comprising 35 patients with CF (mean age, 31 ± 7 yr) before (MRI1) and after (MRI2) at least 1 month (mean duration, 8 ± 4 mo) on ETI therapy and 24 control patients with CF (mean age, 31 ± 7 yr) without ETI. MRI was assessed using the validated chest MRI score, and the presence and total lumen area of BAD were assessed with commercial software. - - Results: The MRI global score was stable in the control group from MRI1 to MRI2 (mean difference, 1.1 [−0.3, 2.4]; P = 0.054), but it was reduced in the ETI group (−10.1 [−0.3, 2.4]; P < 0.001). In the control and ETI groups, BAD was present in almost all patients at baseline (95% and 94%, respectively), which did not change at MRI2. The BAD total lumen area did not change in the control group from MRI1 to MRI2 (1.0 mm2 [−0.2, 2.2]; P = 0.099) but decreased in the ETI group (−7.0 mm2 [−8.9, −5.0]; P < 0.001). This decrease correlated with improvements in the MRI global score (r = 0.540; P < 0.001). - - Conclusions: Our data show that BAD may be partially reversible under ETI therapy in adult patients with CF who have established disease.